Implementasi Regulasi Tentang Surveyor Kadaster Berlisensi dalam Percepatan Pendaftaran Tanah di Kantor Wilayah Badan Pertanahan Provinsi Sumatera Utara - Eko Budi Wahyono (BHUMI: Jurnal Agraria dan Pertanahan, 2017)
Abstract:  This research aim to understand the implementation of the regulation of licensed cadaster surveyor in The Regional Office of National Land Agency of the North Sumatera Province on the acceleration of land registration. The research using qualitative method by describing the results of observation, interview and data of the implementation of accelerated land registration, specifically on the collectors of physical data (PULDASIK – Pengumpul Data Fisik) of the licensed cadastral surveyor, referring to the Regulation of The Minister of Agrarian Affairs and Spatial Planning/Head of National Land Agency Republic of Indonesia Nr. 33 year 2016 and the Regulation of The Minister of Agrarian Affairs and Spatial Planning/Head of National Land Agency Nr. 11 year 2017. The results show that: the implementation of the regulation of Licensed Cadastral Surveyor has not been fully implemented, caused by the limitation of:  the number of KJSKB and SKB;  ASK graduated from D1 PPK-STPN prefer to do apprenticeship so they did not interested in joining KJSKB, and the limitation of financial capability of the KJSKB/SKB. The implementation of the regulation of Licensed Cadastral Surveyor also inhibited by the requirements mentioned on the regulation itself. Moreover, the competency and quality of the SKB is noticed as above the standard, and have unprofessional work ethic. It is recommended to increase the acceptance of Licensed Cadastral Surveyor, and those who already passed the test should forming KJSKB and improve their professionalism by acquiring certificate of competence when they follow the examination to obtain the license. Intisari: Penelitian ini bertujuan untuk mengetahui implementasi regulasi tentang Surveyor Kadaster Berlisensi di Kantor Wilayah Badan Pertanahan Nasional Provinsi Sumatera Utara dalam percepatan pendaftaran tanah. Metode penelitian menggunakan metode kualitatif dengan dideskriptifkan berdasarkan pengamatan, interview, dan data pelaksanaan percepatan pendaftaran tanah khusus pengumpul data fisik (PULDASIK) Surveyor Kadaster Berlisensi dengan berpedoman pada Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia  Nomor 33 Tahun 2016 dan Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 11 Tahun 2017. Diperoleh hasil bahwa implementasi regulasi tentang Surveyor Kadaster Berlisensi belum dijalankan sepenuhnya. Hal ini disebabkan oleh keterbatasan jumlah KJSKB dan SKB, ASK lulusan D1 PPK-STPN lebih menyukai magang sehingga tidak mau bergabung dengan KJSKB dan keterbatasan modal keuangan yang dimiliki KJSKB/SKB. Pelaksanakan regulasi Surveyor Kadaster Berlisensi juga terhambat oleh persyaratan yang ada di dalam regulasi Surveyor Kadaster Berlisensi, kualitas kompetensi SKB rendah, serta sikap kerja tidak profesional. Maka untuk itu direkomendasikan meningkatkan jumlah penerimaan Surveyor Kadaster Berlisensi dan yang telah lulus ujian lisensi untuk segera membentuk KJSKB dan meningkatkan profesionalisme Surveyor Kadaster Berlisensi dengan melengkapi sertipikat kompetensi saat ujian memperoleh lisensi.